How the Fewest Become the Greatest. L. casei’s Impact on Long Ripened Cheeses - Bottari, Benedetta; Levante, Alessia; Neviani, Erasmo; Gatti, Monica (Frontiers in Microbiology, 2018)
Lactobacillus casei group, including species classified currently as L. casei, L. paracasei, and L. rhamnosus, are among the most frequently found species in raw milk, hard cooked, long-ripened cheeses. Starting from very low amounts in raw milk, they become dominant in the cheese during ripening, selected by several technological drivers. Their presence at different stages of cheese making and ripening turned out to be crucial to define cheese features. For these reasons, the scientific community has been more and more busy in studying this “tiny but mighty microbes” and their effect in cheeses. The present paper aims to review the current literature on this topic, with particular reference to the case of Parmigiano Reggiano and Grana Padano, two of the most famous PDO Italian cheeses. Recent advances regarding the possibility to select new wild strains capable to persist to the end of ripening, carrying out a slow but crucial activity and with specific aromatic features, are also presented.